2013
DOI: 10.1111/brv.12032
|View full text |Cite
|
Sign up to set email alerts
|

The role of the circadian system in fractal neurophysiological control

Abstract: Many neurophysiological variables such as heart rate, motor activity, and neural activity are known to exhibit intrinsic fractal fluctuations - similar temporal fluctuation patterns at different time scales. These fractal patterns contain information about health, as many pathological conditions are accompanied by their alteration or absence. In physical systems, such fluctuations are characteristic of critical states on the border between randomness and order, frequently arising from nonlinear feedback intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 192 publications
(290 reference statements)
5
55
0
5
Order By: Relevance
“…Moreover, scale invariance is lost in the behavioral activity fluctuations of aged humans and in Alzheimer's disease patients, and this has been attributed to dysfunction of the SCN (12,28). Together, these results indicate that proper functioning of the SCN is crucial for scale-invariant patterns of activity (14). In the presence of running wheels, the scale-invariant correlation in activity fluctuations was improved in aging mice (1.5-and 2-y group).…”
Section: Summary and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, scale invariance is lost in the behavioral activity fluctuations of aged humans and in Alzheimer's disease patients, and this has been attributed to dysfunction of the SCN (12,28). Together, these results indicate that proper functioning of the SCN is crucial for scale-invariant patterns of activity (14). In the presence of running wheels, the scale-invariant correlation in activity fluctuations was improved in aging mice (1.5-and 2-y group).…”
Section: Summary and Discussionmentioning
confidence: 87%
“…Recent studies showed that scaleinvariant activity patterns are disrupted with aging and in patients suffering from dementia (12). The degree of the disruption is strongly correlated with the circadian neurotransmitter content in the suprachiasmatic nucleus (SCN) (14), the master clock in mammals that regulates circadian rhythms in physiology and behavior (15).…”
mentioning
confidence: 99%
“…Fractality is probably the most well-known index of such complexity (Pittman-Polletta et al, 2013). The self-similar, fractal nature of the human heartbeat was discovered thirty years ago (see the influential article by Goldberger, 1996) although not much research has been carried out to understand the meaning of this fractal feature in psychological anxiety-related fields.…”
Section: Introductionmentioning
confidence: 99%
“…Under stable conditions in health, heart rate is not entirely regular [87]. Physiological heart rate variability (HRV) indicates an adequate connection between the heart and autonomous nervous system, as well as a coupling between 2 important biological oscillators, that is, respiration and heart rate [87,88].…”
Section: Physiological Variabilitymentioning
confidence: 99%
“…The latter is characterized by a 1/f (f = frequency) pattern [88][89][90]. The 1/f pattern, in which the amplitude of the variations is inversely related to its frequency, remains similar over different time scales.…”
Section: Physiological Variabilitymentioning
confidence: 99%